Short videos from movies and tv programs with idiomatic expressions to teach vocabulary - Malavé Ronquillo, Sharid Deyanira (2025)
This research explores the effectiveness of using short videos from movies and TV programs containing idiomatic expressions as a technique to enhance vocabulary acquisition among English language learners at Unidad Educativa Bilingüe Americano. The study identifies the challenges students face in learning vocabulary through traditional methods, which often rely on mechanical memorization without context. It highlights the importance of idiomatic expressions in achieving fluency and comprehension in English, as these expressions are frequently used in everyday communication. The research employs qualitative methods, including interviews with English teachers and students, to gather insights on the impact of multimedia resources on vocabulary learning. Findings indicate that short videos significantly improve students' engagement, motivation, and retention of new vocabulary by providing contextualized learning experiences. Teachers recognize the value of integrating authentic media content to enhance cultural understanding and facilitate natural language use. The study concludes that incorporating short videos into English instruction not only aids in vocabulary comprehension but also fosters a more dynamic and interactive learning environment.